Determining the subcellular compartment in which the unique cleavage of mitochondrial F1 ATPase subunit alpha happens - Andova, Ana-Marija (Jihočeská univerzita, 2020)
The T. brucei's infectious stage is characterized by its unique metabolism which requires the mitochondrial FoF1-ATPase to hydrolyze ATP in order to maintain the essential mitochondrial membrane potential. This complex rotary machine has several extraordinary features including the proteolytic cleavage of the F1-ATPase subunit alpha that results in the expulsion of an internal octapeptide. This thesis is focused on whether the proteolytic processing of the essential F1-ATPase subunit already begins in the cytosol.
Determining the subcellular compartment in which the unique cleavage of mitochondrial F1 ATPase subunit alpha happens
Keywords: Parasitology; trypanosoma brucei; F1 ATPase; subunit alpha; Parasitology; trypanosoma brucei; F1 ATPase; subunit alpha